2013
DOI: 10.1007/s10067-013-2334-z
|View full text |Cite
|
Sign up to set email alerts
|

Profile of inflammatory mediators in tonsils of patients with periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome

Abstract: The purpose of this study was to analyze the levels of white blood cells and profile of proinflammatory Th1, Th2, Th17, and T regulatory tissue cytokines in the tonsils of periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) patients to contribute to the pathophysiological understanding of the PFAPA syndrome. A cohort of PFAPA patients who had tonsillectomy during 2010 and 2011 was included and compared to control patients who had tonsillectomy for tonsillar hypertrophy. White blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
5
16
2
1
Order By: Relevance
“…Our case series is similar to others in the literature regarding most frequent clinical symptoms (Feder and Salazar, 2010 Feb;Marshall et al, 1987;Tasher et al, 2006). A recurrence of aphthous stomatitis in PFAPA patients after surgery has been previously described in some studies (Valenzuela et al, 2013;Pignataro et al, 2009;Vigo et al, 2014), but this was not a finding of our study. The median age at surgery in PFAPA patients was also similar to that reported in other series (Feder and Salazar, 2010;Valenzuela et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our case series is similar to others in the literature regarding most frequent clinical symptoms (Feder and Salazar, 2010 Feb;Marshall et al, 1987;Tasher et al, 2006). A recurrence of aphthous stomatitis in PFAPA patients after surgery has been previously described in some studies (Valenzuela et al, 2013;Pignataro et al, 2009;Vigo et al, 2014), but this was not a finding of our study. The median age at surgery in PFAPA patients was also similar to that reported in other series (Feder and Salazar, 2010;Valenzuela et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…A recently published study exploring the tonsils of patients with PFAPA examined mRNA expression of various cytokines and found IL-1␤, TNF-␣, TGF-␤, IL-17 and IFN-␥ mRNA levels that were similar to control hypertrophic tonsils, with the only exception of IL-4 being lower in the PFAPA tonsils (Valenzuela et al, 2013). Chen et al (Chen et al, 2009) investigated the tissue sections of patients with autoinflammatory syndromes including one tonsil from a patient with PFAPA and found that the tonsil of the PFAPA patient contained more basophils with bound or internalised IgD.…”
Section: Discussionmentioning
confidence: 84%
“…Можно предположить: либо миндалины вы-ступают первичными центрами иммунной дисре-гуляции, либо микробиота миндалин становится триггером иммунной дисрегуляции у предраспо-ложенных индивидуумов. Во всяком случае, ни одно из проведенных исследований не позволило определить истинный механизм или вероятный триггер аутовоспаления [24][25][26][27]. Несмотря на схожий спектр цитокинов при инфекционном воспалении и аутовоспалении, клеточные реак-ции различны.…”
Section: патогенезunclassified
“…Although the pathogenesis of PFAPA syndrome is not fully understood, it is evaluated in autoinflammatory syndromes. Studies have shown that IL-1β, IL-18, tumor necrosis factor-α, interferon (IFN)-γ from proinflammatory cytokines increase in the early phase of fever and IL-6 increases rapidly in the late phase (7)(8)(9)(10)(11)(12). In contrast, levels of T-cell-associated cytokines IL-7, IL-17 and anti-inflammatory cytokines IL-10 and IL-4 decrease during exacerbation (8).…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, increased expression of inflammation-associated genes (AIM2, CASP1) and IL-1 were detected during the episode (11). In the fever episodes, dysregulation in natural immunity together with an increase in Th1 response, and reduction in Th2 response lead to changes in cytokine levels (8)(9)(10)12). Increased levels of monocytes, and decreased levels of eosinophiles and lymphocytes are observed during exacerbations (9,10).…”
Section: Pathogenesismentioning
confidence: 99%